7.5.42 problem 42

Internal problem ID [146]
Book : Elementary Differential Equations. By C. Henry Edwards, David E. Penney and David Calvis. 6th edition. 2008
Section : Chapter 1. First order differential equations. Section 1.6 (substitution and exact equations). Problems at page 72
Problem number : 42
Date solved : Friday, February 07, 2025 at 07:58:30 AM
CAS classification : [[_1st_order, _with_linear_symmetries], _exact, _rational]

\begin{align*} \frac {2 x^{{5}/{2}}-3 y^{{5}/{3}}}{2 x^{{5}/{2}} y^{{2}/{3}}}+\frac {\left (3 y^{{5}/{3}}-2 x^{{5}/{2}}\right ) y^{\prime }}{3 x^{{3}/{2}} y^{{5}/{3}}}&=0 \end{align*}

Solution by Maple

Time used: 0.016 (sec). Leaf size: 181

dsolve(( (2*x^(5/2)-3*y(x)^(5/3))/( 2*x^(5/2)*y(x)^(2/3)) )+(   (3*y(x)^(5/3)-2*x^(5/2))/( 3*x^(3/2)*y(x)^(5/3) ) )*diff(y(x),x)=0,y(x), singsol=all)
 
\begin{align*} y &= \frac {2^{{3}/{5}} 3^{{2}/{5}} \left (x^{{5}/{2}}\right )^{{3}/{5}}}{3} \\ y &= -\frac {\left (i \sqrt {2}\, \sqrt {5-\sqrt {5}}+\sqrt {5}+1\right )^{3} 2^{{3}/{5}} 3^{{2}/{5}} \left (x^{{5}/{2}}\right )^{{3}/{5}}}{192} \\ y &= \frac {\left (i \sqrt {2}\, \sqrt {5-\sqrt {5}}-\sqrt {5}-1\right )^{3} 2^{{3}/{5}} 3^{{2}/{5}} \left (x^{{5}/{2}}\right )^{{3}/{5}}}{192} \\ y &= -\frac {\left (i \sqrt {2}\, \sqrt {5+\sqrt {5}}-\sqrt {5}+1\right )^{3} 2^{{3}/{5}} 3^{{2}/{5}} \left (x^{{5}/{2}}\right )^{{3}/{5}}}{192} \\ y &= \frac {\left (i \sqrt {2}\, \sqrt {5+\sqrt {5}}+\sqrt {5}-1\right )^{3} 2^{{3}/{5}} 3^{{2}/{5}} \left (x^{{5}/{2}}\right )^{{3}/{5}}}{192} \\ \frac {x}{y^{{2}/{3}}}+\frac {y}{x^{{3}/{2}}}+c_1 &= 0 \\ \end{align*}

Solution by Mathematica

Time used: 0.081 (sec). Leaf size: 260

DSolve[( (2*x^(5/2)-3*y[x]^(5/3))/( 2*x^(5/2)*y[x]^(2/3)) )+(   (3*y[x]^(5/3)-2*x^(5/2))/( 3*x^(3/2)*y[x]^(5/3) ) )*D[y[x],x]==0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to \left (\frac {2}{3}\right )^{3/5} \left (x^{5/2}\right )^{3/5} \\ y(x)\to c_1 x^{3/2} \\ y(x)\to -\left (-\frac {2}{3}\right )^{3/5} x^{3/2} \\ y(x)\to \left (-\frac {2}{3}\right )^{3/5} x^{3/2} \\ y(x)\to -\left (\frac {2}{3}\right )^{3/5} x^{3/2} \\ y(x)\to \left (\frac {2}{3}\right )^{3/5} x^{3/2} \\ y(x)\to -\sqrt [5]{-1} \left (\frac {2}{3}\right )^{3/5} x^{3/2} \\ y(x)\to \sqrt [5]{-1} \left (\frac {2}{3}\right )^{3/5} x^{3/2} \\ y(x)\to -(-1)^{2/5} \left (\frac {2}{3}\right )^{3/5} x^{3/2} \\ y(x)\to (-1)^{2/5} \left (\frac {2}{3}\right )^{3/5} x^{3/2} \\ y(x)\to -(-1)^{4/5} \left (\frac {2}{3}\right )^{3/5} x^{3/2} \\ y(x)\to (-1)^{4/5} \left (\frac {2}{3}\right )^{3/5} x^{3/2} \\ y(x)\to \left (\frac {2}{3}\right )^{3/5} \left (x^{5/2}\right )^{3/5} \\ \end{align*}